1997
DOI: 10.1145/262793.262813
|View full text |Cite
|
Sign up to set email alerts
|

The incredible shrinking pipeline

Abstract: The ratio of women involved incomputer science from high school to graduate school has been dwindling at a startling pace over the past decade. Is there hope in sight? COMMUNICATIONS OF THE ACM October I 997/Vol 40. No. I 0 103

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
146
0
8

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(170 citation statements)
references
References 1 publication
9
146
0
8
Order By: Relevance
“…Almost every area of science and engineering has experienced substantial increases in the enrollment of female undergraduates over the last few decades. However, the percentage of undergraduate majors in computer science (CS) who are female has declined from 30-40% in the 1980's to 15-20% today [2,4]. Since this trend is unique to computing, it is important to understand the factors behind the decrease.…”
Section: Introductionmentioning
confidence: 99%
“…Almost every area of science and engineering has experienced substantial increases in the enrollment of female undergraduates over the last few decades. However, the percentage of undergraduate majors in computer science (CS) who are female has declined from 30-40% in the 1980's to 15-20% today [2,4]. Since this trend is unique to computing, it is important to understand the factors behind the decrease.…”
Section: Introductionmentioning
confidence: 99%
“…The barriers emerging from the survey have been well canvassed in the literature [2], [3]. The message, both within the secondary schools and the community, has not yet been heard.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be no intrinsic reason why women would not choose to study Computer Science [3]. Other authors have identified issues that are important to the recruitment of women into Computer Science courses [2). Social background, local role models, interest, ability level, and recruitment measures aimed at women have been identified as crucial in any attempt to encourage females to study Computer Science [7].…”
Section: Introductionmentioning
confidence: 99%
“…This trend is similar in other European countries and the USA. (Grundy 1996, RichardsonlKavanagh 1997, Rasmussen 1997, Camp 1997). …”
Section: Women In German Informatics Educationmentioning
confidence: 99%